2022
DOI: 10.1155/2022/3734707
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Competitive Advantage through Corporate Social Responsibility (CSR) and Green Behavior Strategies

Abstract: Driven by the pursuit of sustainable competitive advantage and consideration of the impact of corporate social responsibility activities on society and the need for environmentally friendly behaviors to improve companies’ sustainable performance, this study investigates the impact of corporate social responsibility (CSR) on firm performance through the use of green behavior. An empirical survey was carried out, data was collected from 176 respondents, constituting a 61.8% response rate of the sample of 278 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(96 reference statements)
1
9
0
Order By: Relevance
“…So the manufacturing, oil refineries and service industries encourage its employee in sustainability-related activities. This finding is reliable to the resells of previous that revealed CSR is positively related to PEN (Wells et al , 2016; Abubakar et al , 2022). The study also confirmed that CSR is the critical driver of EGB.…”
Section: Discussionsupporting
confidence: 90%
“…So the manufacturing, oil refineries and service industries encourage its employee in sustainability-related activities. This finding is reliable to the resells of previous that revealed CSR is positively related to PEN (Wells et al , 2016; Abubakar et al , 2022). The study also confirmed that CSR is the critical driver of EGB.…”
Section: Discussionsupporting
confidence: 90%
“…As the concept of sustainable development takes root in people's minds, companies are receiving increasing attention for their actions related to social responsibility, such as environmental protection, employee welfare, and community service (Abubakar et al, 2022;Brammer et al, 2007;Carlini et al, 2019). More and more companies are voluntarily disclosing their sustainability reports to meet the information needs of investors (Albareda et al, 2007;Mahoney et al, 2013;Torugsa et al, 2012Torugsa et al, , 2013, and in some countries (such as China and France), companies are even mandated to publish their sustainability reports (Chen et al, 2018;Habek & Wolniak, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The predisposition to accept the dynamic norms and expectations is normative influence. In contrast, the degree to which one acquires service and product information from competent individuals is called informational influence (also known as informational learning) ( Zhang et al, 2015 ; Abubakar et al, 2022 ). EWOM communications impacted by SNS friends’ norms and values influence customers who are sensitive to normative impacts.…”
Section: Literature and Research Hypothesesmentioning
confidence: 99%